A method for synthesizing a highly dispersed catalytic combustion catalyst
Patent Information
- Application Number
- CN202611096035.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-08-18
AI Technical Summary
[0006]本发明的目的在于提供一种高分散的催化燃烧催化剂合成方法,用于解决现有氢催化燃烧催化剂在强放热运行中导热散热不足、氧化铝类载体层结合力弱、铂基双金属或多金属活性组分分散度低以及贵金属颗粒易团聚的技术问题
[0041]The surface activation treatment of this invention transforms the surface of the high thermal conductivity substrate from a smooth, inert state to a rough, activated state, providing an interfacial basis for the nucleation and adhesion of the alumina precursor second carrier layer. Compared with direct coating, the bonding between the alumina precursor second carrier layer and the high thermal conductivity substrate is more stable and less prone to detachment during thermal cycling and airflow erosion. The alumina precursor second carrier layer adopts nanosheet, nanorod, porous spherical, or composite morphologies, providing not only specific surface area but also different types of anchoring points and mass transfer channels. Nanosheet structures are beneficial for increasing the number of edge sites, nanorod structures are beneficial for forming open channels, and porous spherical structures are beneficial for improving the loading capacity of the loading liquid.
Smart Images

Figure CN122583000A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogen catalytic combustion technology, specifically relating to a method for synthesizing a highly dispersed catalytic combustion catalyst. Background Technology
[0002] Hydrogen catalytic combustion utilizes a solid catalyst to lower the activation energy of the hydrogen-oxygen reaction, enabling hydrogen to undergo a flameless oxidation reaction at a lower temperature. Compared to open flame combustion, hydrogen catalytic combustion is more suitable for applications such as hydrogen-containing exhaust gas treatment, hydrogen removal from fuel cell exhaust gases, and small-scale heating devices.
[0003] Existing hydrogen catalytic combustion catalysts typically consist of a support and a noble metal active component. Alumina supports have a certain specific surface area, enabling them to support noble metal active components such as platinum, palladium, rhodium, and ruthenium. However, alumina supports have limited thermal conductivity, and during the exothermic process of hydrogen catalytic combustion, localized hot spots easily form on the surface of catalyst particles and within the catalyst bed. These localized hot spots promote the migration, agglomeration, and sintering of noble metal particles, resulting in a reduction of active sites and further deterioration of the temperature distribution.
[0004] Materials such as silicon carbide, silicon nitride, aluminum nitride, stainless steel, nickel-based alloys, nickel foam, and hexagonal boron nitride can improve heat dissipation, but these materials often have relatively inert surfaces and low specific surface areas. When noble metal precursors are directly impregnated onto the surfaces of these materials, the distribution of platinum-based bimetallic or multimetallic active components is uneven, and the bonding force between metal particles and the carrier is insufficient. After high-temperature exothermic reactions and airflow scouring, agglomeration, detachment, or localized deactivation easily occurs. Coating the surface of a high thermal conductivity substrate with an alumina coating can supplement the specific surface area, but conventional slurry coatings mostly rely on mechanical adhesion. The nucleation bonding between the alumina coating and the high thermal conductivity substrate is insufficient, and differences in thermal expansion and repeated temperature rises and falls can cause cracking or peeling. When the alumina coating has a uniform morphology, it is also difficult to simultaneously achieve gas mass transfer, anchoring of platinum-based bimetallic or multimetallic active components, and heat dissipation.
[0005] The precious metal loading process also affects the stability of hydrogen catalytic combustion catalysts. In conventional impregnation methods, solvent migration easily occurs during drying, causing the metal precursor to accumulate on the outer surface along the evaporation front, forming larger metal particles after calcination and reduction. While single platinum active components exhibit high activity, the large amount of precious metals required leaves room for improvement in anti-sintering performance. Summary of the Invention
[0006] The purpose of this invention is to provide a method for synthesizing a highly dispersed catalytic combustion catalyst, which solves the technical problems of insufficient heat conduction and heat dissipation in existing hydrogen catalytic combustion catalysts during strong exothermic operation, weak bonding force of alumina-based support layers, low dispersion of platinum-based bimetallic or multimetallic active components, and easy agglomeration of noble metal particles.
[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0008] A method for synthesizing a highly dispersed catalytic combustion catalyst includes the following steps.
[0009] S1. A high thermal conductivity substrate is selected and surface-activated to form a roughened activated surface. The roughened activated surface possesses a porous structure, a rough structure, and surface active sites. Surface active sites include at least one of hydroxyl sites, oxidation active sites, etching defect sites, or polar functional group sites. Hydroxyl sites refer to hydroxyl-containing surface locations capable of forming hydrogen bonds or condensation bonds with aluminum source hydrolysis products; oxidation active sites refer to metal oxide or non-metal oxide surface locations that, after oxidation treatment, can improve the adhesion of the aluminum source; etching defect sites refer to micro-pits, micro-cracks, or micro-roughness locations formed by plasma, laser, or chemical etching; polar functional group sites refer to surface locations formed by oxygen-containing, nitrogen-containing, or other polar groups. The roughened activated surface provides nucleation and adhesion sites for the alumina precursor.
[0010] S2. The surface-activated high thermal conductivity substrate is placed in a second carrier construction system, which is a reaction system for forming the alumina precursor second carrier layer. The alumina precursor second carrier layer is formed on the surface of the high thermal conductivity substrate, resulting in a composite carrier. The alumina precursor second carrier layer has at least one morphology selected from nanosheets, nanorods, and porous spheres. The nanosheet structure provides edge anchoring points, the nanorod structure forms open mass transfer channels, and the porous sphere structure provides pore volume and loading space. Through morphological coordination, the alumina precursor second carrier layer simultaneously undertakes the functions of anchoring platinum-based bimetallic or multimetallic active components and gas mass transfer.
[0011] S3. After pre-drying the composite support at 60℃ to 100℃ for 0.5h to 2h, the composite support is contacted with a supported system containing platinum precursors and alloy metal precursors. This allows platinum and alloy metals to form platinum-based bimetallic or multimetallic active components on the surface of the second support layer of the alumina precursor, thus obtaining a supported catalyst. Platinum is used to provide active sites for hydrogen adsorption and dissociation, while the alloy metal is used to adjust the electronic structure around the platinum and the stability of the metal particles.
[0012] S4. The supported catalyst is subjected to gradient drying treatment, which gradually removes the solvent from the outer surface of the composite support and the surface and internal structure of the second support layer of the alumina precursor. Gradient drying treatment reduces the migration and enrichment of the precursor due to rapid solvent evaporation, which is beneficial to maintaining the uniform distribution of platinum-based bimetallic or multimetallic active components in the second support layer of the alumina precursor.
[0013] S5. The supported catalyst after gradient drying is subjected to calcination and reduction activation treatments sequentially. Calcination transforms the alumina precursor second support layer into a nano-alumina second support layer and removes residual organic components. Reduction activation treatment causes the platinum-based bimetallic or multimetallic active components to form a metallic state, a platinum-based alloy structure, or a bimetallic or multimetallic synergistic structure with platinum and alloy metals distributed adjacently. After treatment, a hydrogen catalytic combustion catalyst with high thermal conductivity is obtained.
[0014] The high thermal conductivity substrate support serves as the reaction heat conduction framework for the high thermal conductivity hydrogen catalytic combustion catalyst. The high thermal conductivity substrate support can be selected from at least one of metal-based supports, ceramic-based supports, and carbon-based supports.
[0015] Metal-based supports include copper, stainless steel, pure aluminum, aluminum alloys, nickel-based alloys, and nickel foam. Ceramic-based supports include silicon carbide, silicon nitride, aluminum nitride, hexagonal boron nitride, and high-purity alumina. Carbon-based supports include graphite, expanded graphite, graphene, and carbon nanotubes.
[0016] The high thermal conductivity substrate can be spherical, columnar, sheet-like, honeycomb, foam, Raschig ring, Pall ring, or granular / block-like. Spherical, columnar, and granular / block-like substrates are suitable for fixed-bed packing; honeycomb and foam substrates are suitable for handling low-pressure-drop hydrogen-containing gases; sheet-like substrates are suitable for integration with heat exchanger walls. The pore density of honeycomb substrates can range from 200 cells / in² to 600 cells / in²; the pore density of foam substrates can range from 10 ppi to 60 ppi. Cell / in² represents the number of pores per square inch, and ppi represents the number of pores per inch.
[0017] Surface activation treatment includes at least one of plasma modification, laser modification, ozone coupled roasting modification, and chemical corrosion modification.
[0018] Plasma modification is suitable for introducing active sites on the surfaces of ceramic-based, carbon-based, and some metal-based supports. Laser modification is suitable for forming micro-pits and etched textures. Ozone-coupled roasting modification is suitable for mild oxidation activation. Chemical etching modification is suitable for forming micro-rough structures on the surfaces of stainless steel, nickel-based alloys, aluminum alloys, and nickel foam.
[0019] The surface of the high thermal conductivity substrate after surface activation treatment preferably meets at least one of the following conditions: a water contact angle of 20° to 75° measured by the deionized water droplet method at 25°C ± 2°C; and a surface roughness Ra of 0.2 μm to 3.0 μm measured by a contact profilometer. A lower water contact angle indicates improved wetting ability of the high thermal conductivity substrate surface for the aluminum-containing liquid phase system, while an increased surface roughness Ra indicates an increase in the geometrical locations available for alumina precursor nucleation and attachment on the high thermal conductivity substrate surface. These ranges enable a more uniform adhesion of the alumina precursor second carrier layer on the high thermal conductivity substrate surface, while avoiding excessive etching that could reduce the mechanical strength of the high thermal conductivity substrate.
[0020] After S2 treatment, the mass increment of the second carrier layer of the alumina precursor relative to the high thermal conductivity substrate is preferably 0.5 wt% to 20 wt%. When the mass increment is less than 0.5 wt%, the anchoring points provided by the second carrier layer of the alumina precursor are insufficient; when the mass increment is greater than 20 wt%, the second carrier layer of the alumina precursor is too thick, which may increase the gas mass transfer resistance and weaken the rapid heat conduction effect of the high thermal conductivity substrate.
[0021] The second carrier layer of the alumina precursor is formed by hydrothermal morphology controllable synthesis, alumina hydrate slurry coating, sol-gel deposition, vacuum impregnation, or low-temperature vapor deposition.
[0022] In the hydrothermal morphology-controllable synthesis method, a surface-activated, high-thermal-conductivity substrate can be placed in a hydrothermal reaction system containing an aluminum source, a precipitant, and a morphology modifier. The aluminum source can be aluminum nitrate, aluminum chloride, aluminum isopropoxide, aluminum sulfate, or aluminum sol. The precipitant can be urea, ammonia, hexamethylenetetramine, or ammonium carbonate. The morphology modifier can be at least one of urea, polyvinylpyrrolidone, citric acid, ethylenediamine, or glucose. The aluminum source concentration can be from 0.1 mol / L to 0.8 mol / L, the molar ratio of aluminum source to precipitant can be from 1:1.5 to 1:4, the hydrothermal temperature can be from 120℃ to 200℃, and the hydrothermal reaction time can be from 6 h to 24 h.
[0023] When using the alumina hydrated slurry coating method, boehmite, alumina sol, deionized water, pore-forming agent, and binder are mixed to form an alumina hydrated slurry, which is then adhered to the surface of a high thermal conductivity substrate by dip coating, spraying, spin coating, or vacuum-assisted adsorption. The solid content of the alumina hydrated slurry can be 35wt% to 65wt%, the stirring rate can be 200r / min to 500r / min, the stirring time can be 30min to 90min, the coating thickness can be 5μm to 30μm, the pre-drying temperature after coating can be 60℃ to 100℃, and the pre-drying time can be 0.5h to 2h. r / min represents revolutions per minute.
[0024] When using the sol-gel deposition method, aluminum alkoxide sol or aluminum salt hydrolysate sol can be used to form a gel layer on the surface of a high thermal conductivity substrate, followed by aging, drying, and calcination to form a second nano-alumina carrier layer. The viscosity of the aluminum alkoxide sol or aluminum salt hydrolysate sol can be from 10 mPa·s to 50 mPa·s, the aging temperature can be from 20℃ to 60℃, and the aging time can be from 2 h to 12 h.
[0025] When using the vacuum impregnation method, the surface-activated high thermal conductivity substrate can be placed under vacuum conditions, followed by the introduction of alumina precursor sol or aluminum source solution, allowing the alumina precursor sol or aluminum source solution to penetrate the rough and porous structures on the surface of the high thermal conductivity substrate. The vacuum level can be from 5 Pa to 50 Pa, the impregnation time can be from 10 min to 120 min, and the settling time after returning to normal pressure can be from 10 min to 120 min.
[0026] When using low-temperature vapor deposition, aluminum-containing precursors can be deposited on the surface of a high thermal conductivity substrate under low-pressure conditions. The deposition temperature can range from 80°C to 350°C, the deposition vacuum can range from 5Pa to 50Pa, the carrier gas flow rate can range from 20 sccm to 80 sccm, and the deposition time can range from 20 min to 90 min. sccm represents standard cubic centimeters per minute.
[0027] The morphological parameters of the second carrier layer of the alumina precursor are as follows: the thickness of the nanosheet-like second carrier layer of the alumina precursor is 5 nm to 30 nm and the diameter is 100 nm to 400 nm; the diameter of the nanorod-like second carrier layer of the alumina precursor is 20 nm to 80 nm, the length is 150 nm to 600 nm, and the aspect ratio is 3:1 to 10:1; the particle size of the porous spherical second carrier layer of the alumina precursor is 200 nm to 800 nm, the average pore size is 5 nm to 30 nm, and the porosity is 30% to 65%.
[0028] Platinum-based bimetallic or polymetallic active components are the main active centers for hydrogen catalytic combustion. Platinum can adsorb and dissociate hydrogen, and the active sites of platinum can be modulated by the alloy metal through electronic, geometric, or interfacial effects. Platinum-based bimetallic or polymetallic active components include at least one of Pt-Ni, Pt-Co, Pt-Cu, Pt-Ru, Pt-Pd, Pt-Rh, Pt-Ni-Co, and Pt-Ni-Cu. The Pt mass loading in the platinum-based bimetallic or polymetallic active component can be from 0.1 wt% to 5 wt%, and the molar ratio of Pt to the alloy metal can be from 1:0.2 to 1:4.
[0029] The platinum-containing precursor can be at least one of chloroplatinic acid, platinum nitrate, platinum acetylacetonate, and potassium chloroplatinate. The alloy metal precursor can be nickel nitrate, cobalt nitrate, copper nitrate, ruthenium chloride, palladium nitrate, rhodium chloride, ferric nitrate, or a corresponding metal acetylacetonate. The preferred supporting system is an ethylene glycol mixed solution. The pH of the ethylene glycol mixed solution is 8 to 12, the pH adjuster is at least one of ammonia, sodium hydroxide, and urea, the reaction temperature is 120°C to 180°C, the reflux time is 60 min to 240 min, and the stirring rate is 150 r / min to 400 r / min. Ethylene glycol acts as both a solvent and a mild reducing agent, enabling platinum and alloy metals to nucleate in situ on the surface of the second carrier layer of the alumina precursor.
[0030] Platinum-based bimetallic or multimetallic active components, after reduction and activation treatment, form platinum-based alloy structures, or bimetallic or multimetallic synergistic structures with platinum and alloy metals distributed adjacently. The reduction and activation treatment temperature for forming platinum-based alloy structures can be from 450℃ to 800℃. The reduction and activation treatment temperature for forming bimetallic or multimetallic synergistic structures can be from 200℃ to 450℃. Platinum-based alloy structures or bimetallic or multimetallic synergistic structures can be confirmed by X-ray diffraction, transmission electron microscopy, energy dispersive spectroscopy (EDS), or X-ray photoelectron spectroscopy.
[0031] The gradient drying process includes a low-temperature conformal drying stage and a medium-temperature solvent removal drying stage. The low-temperature conformal drying stage has a drying temperature of 25℃ to 60℃ and a drying time of 2h to 8h; the medium-temperature solvent removal drying stage has a drying temperature of 60℃ to 120℃ and a drying time of 4h to 16h. The heating rate from the low-temperature conformal drying stage to the medium-temperature solvent removal drying stage can be 1℃ / min to 5℃ / min. The surface gas flow rate during the gradient drying process can be 0m³ / h to 400m³ / h. For honeycomb carriers, foam carriers, and Pall ring carriers, the surface gas flow rate is used to reduce local solvent residue within the pores and enrichment on the outer surface.
[0032] The calcination treatment is carried out in an air, nitrogen, argon, or vacuum atmosphere at a temperature of 200°C to 800°C for 1 to 24 hours. The reduction activation treatment is carried out in a pure hydrogen atmosphere, a hydrogen / nitrogen reducing mixture, or a hydrogen / argon reducing mixture, with a hydrogen volume concentration of 1 vol% to 100 vol%, a reduction temperature of 200°C to 800°C, and a reduction time of 1 to 24 hours.
[0033] The high thermal conductivity hydrogen catalytic combustion catalyst obtained by the above preparation method comprises a high thermal conductivity substrate, a nano-alumina second support layer, and a platinum-based bimetallic or multimetallic active component. The high thermal conductivity substrate forms the heat conduction channel for the reaction, the nano-alumina second support layer forms the anchoring sites for the active component, and the platinum-based bimetallic or multimetallic active component forms the active sites for hydrogen catalytic combustion. These three components form a structural relationship characterized by the combined effects of thermal conduction, interfacial anchoring, and catalytic reaction.
[0034] In a preferred embodiment, after the composite carrier is subjected to ultrasonic treatment at a frequency of 40 kHz and a power of 100 W for 30 min, the shedding rate of the nano-alumina second carrier layer is no higher than 10%. The shedding rate of the nano-alumina second carrier layer is used to characterize the interfacial bonding between the nano-alumina second carrier layer and the high thermal conductivity substrate carrier.
[0035] Furthermore, in S2, cerium precursor and zirconium precursor are added to the second carrier construction system, and the total molar ratio of cerium, zirconium and aluminum in the system is 0.05~0.25:1; in S5, after the calcination treatment and reduction activation treatment, a cerium-zirconium solid solution phase with lattice distortion is precipitated in situ inside the second carrier layer of nano-alumina.
[0036] The degree of lattice mismatch strain formed between the cerium-zirconium solid solution phase and the second nano-alumina carrier layer is controlled by the following mismatch strain formula:
[0037]
[0038] in, For lattice mismatch strain, The average lattice constant of the cerium-zirconium solid solution phase is given. The average lattice constant of the second carrier layer of nano-alumina;
[0039] By controlling the heating rate and maximum temperature of the calcination process, the lattice mismatch strain degree is... The oxygen vacancies at the interface lattice induced by the lattice mismatch strain are maintained between 2.5% and 5.8% to serve as electron acceptor confinement centers for the platinum-based bimetallic or multimetallic active components, forming strong interaction bonds that prevent the aggregation of active metals. Furthermore, the optical phonon scattering effect caused by the lattice distortion region synergistically weakens the interfacial thermal stress between the nano-alumina second carrier layer and the high thermal conductivity substrate carrier under a localized exothermic environment.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The surface activation treatment of this invention transforms the surface of the high thermal conductivity substrate from a smooth, inert state to a rough, activated state, providing an interfacial basis for the nucleation and adhesion of the alumina precursor second carrier layer. Compared with direct coating, the bonding between the alumina precursor second carrier layer and the high thermal conductivity substrate is more stable and less prone to detachment during thermal cycling and airflow erosion. The alumina precursor second carrier layer adopts nanosheet, nanorod, porous spherical, or composite morphologies, providing not only specific surface area but also different types of anchoring points and mass transfer channels. Nanosheet structures are beneficial for increasing the number of edge sites, nanorod structures are beneficial for forming open channels, and porous spherical structures are beneficial for improving the loading capacity of the loading liquid.
[0042] The platinum-based bimetallic or multimetallic active component of this invention can maintain the catalytic activity of platinum while adjusting the structure around the platinum through alloying metals. Compared with a single platinum active component, the platinum-based bimetallic or multimetallic active component is more beneficial in reducing the risk of particle migration and agglomeration during high-temperature operation.
[0043] Gradient drying restricts the metal precursor from concentrating on the outer surface as the solvent evaporates, ensuring a relatively uniform distribution of the platinum-based bimetallic or multimetallic active components on the surface and within the internal structure of the second carrier layer of the alumina precursor. Calcination and reduction activation further enhance the interfacial bonding between the nano-alumina second carrier layer, the platinum-based bimetallic or multimetallic active components, and the highly thermally conductive substrate.
[0044] The high thermal conductivity hydrogen catalytic combustion catalyst of this invention can conduct the reaction heat generated by hydrogen catalytic combustion along a high thermal conductivity substrate, reducing the risk of local hot spot formation, and maintain a high degree of dispersion of active components through a nano-alumina second support layer. This high thermal conductivity hydrogen catalytic combustion catalyst can be used in hydrogen catalytic combustion, hydrogen removal from fuel cell exhaust gas, hydrogen heating, industrial hydrogen-containing exhaust gas treatment, or distributed hydrogen energy heating devices. Attached Figure Description
[0045] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.
[0046] Figure 1 This is a process flow diagram of the method described in this invention.
[0047] Figure 2 This is a schematic diagram showing the structural relationship between the high thermal conductivity substrate carrier, the nano-alumina second carrier layer, and the platinum-based bimetallic or multimetallic active components of the present invention.
[0048] Figure 3 This is a schematic diagram of the interfacial synergy and thermal conduction path between the high thermal conductivity substrate carrier, the nano-alumina second carrier layer, and the platinum-based bimetallic or multimetallic active components of the present invention.
[0049] Figure 4 This is a schematic diagram of the morphology construction of the second carrier layer of the alumina precursor of the present invention.
[0050] Figure 5 This is a schematic diagram illustrating the treatment of the supported catalyst by gradient drying, calcination, and reduction activation processes according to the present invention. Detailed Implementation
[0051] In the following description, only certain exemplary embodiments are briefly described. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of the embodiments of the invention. Therefore, the drawings and description are considered to be exemplary in nature and not restrictive.
[0052] The following is in conjunction with the appendix Figures 1-5 The embodiments of the present invention will be described in detail below.
[0053] Example 1: This example discloses a sheet-like alumina composite silicon carbide-based Pt-Ni catalyst, and the specific preparation method is as follows:
[0054] 20g of 2mm spherical silicon carbide support was washed sequentially with deionized water and ethanol, and dried at 80℃ for 2 hours to obtain a clean silicon carbide support. The clean silicon carbide support was placed in a plasma treatment chamber and surface activation treatment was performed using oxygen plasma. The discharge power was 150W, the working vacuum was 20Pa, the oxygen flow rate was 50sccm, the treatment time was 20min, and the discharge frequency was 10kHz to 40kHz. In this embodiment, the discharge frequency was 20kHz. After treatment, a rough activated surface was formed on the surface of the silicon carbide support.
[0055] The plasma-treated silicon carbide support was placed in a hydrothermal reactor, and 100 mL of a 0.4 mol / L aluminum nitrate aqueous solution was added. Urea was used as a precipitant and morphology modifier, with a molar ratio of aluminum nitrate to urea of 1:3. The hydrothermal reaction was carried out at 180 °C for 6 h, allowing the aluminum source to nucleate in situ on the surface of the silicon carbide support and grow into a lamellar alumina precursor second support layer. After the hydrothermal reaction was completed, the composite support was removed, washed with deionized water until the washing solution was nearly neutral, and pre-dried at 80 °C for 1 h. The resulting lamellar alumina precursor second support layer had a thickness of 12 nm and a diameter of 220 nm.
[0056] Prepare a 50 mL mixed solution of chloroplatinic acid, nickel nitrate, and ethylene glycol to achieve a theoretical Pt loading of 0.6 wt% and a Pt to Ni molar ratio of 1:2. Add the composite support to the ethylene glycol solution, adjust the pH of the system to 9.5 using ammonia, and reflux in an oil bath at 140 °C for 3 h with stirring at a rate of 300 r / min. This allows the ethylene glycol to perform in-situ liquid-phase reduction of the platinum and nickel precursors, forming a Pt-Ni type platinum-based bimetallic or multimetallic active component on the surface of the second support layer of the lamellar alumina precursor. After the reaction is complete, cool to room temperature, filter to separate the solid, and wash sequentially with ethanol and deionized water.
[0057] The filtered supported catalyst was subjected to gradient drying in a vacuum oven. First, it was dried at 40℃ for 6 hours, then the temperature was increased to 80℃ at a rate of 2℃ / min and dried for another 8 hours. The air flow rate was controlled at 120 m³ / h during the drying process. This air flow rate was the circulating air volume of the drying equipment, used to maintain the uniformity of the drying environment. After drying, the sample was placed in a tube furnace and heated to 550℃ at a rate of 5℃ / min, then calcined at 550℃ in air for 3 hours. After calcination, the atmosphere was switched to a 10 vol% hydrogen / nitrogen reducing mixed atmosphere at a flow rate of 100 mL / min, and the temperature was increased to 420℃ at a rate of 5℃ / min. Reduction was carried out at 420℃ for 4 hours to obtain a plate-like alumina composite silicon carbide-based Pt-Ni catalyst.
[0058] Table 1 Key Material Input Table for Example 1:
[0059]
[0060] In Example 1, the silicon carbide support provides a heat conduction path for the reaction, the sheet-like nano-alumina second support layer provides edge anchoring points, and the Pt-Ni type platinum-based bimetallic or multimetallic active component provides active sites for hydrogen catalytic combustion.
[0061] Example 2: This example discloses a porous spherical alumina composite honeycomb silicon nitride-based Pt-Co catalyst, and the specific preparation method is as follows:
[0062] A 200-cell / in² honeycomb silicon nitride support was cut into Φ20mm×10mm cylinders, washed sequentially with deionized water and ethanol, and then dried. The honeycomb silicon nitride support was then subjected to ozone-coupled calcination pretreatment at an ozone concentration of 120 mg / L, a treatment temperature of 40℃, and a treatment time of 40 min. Subsequently, it was calcined at 600℃ for 2 h under a nitrogen atmosphere to obtain a surface-activated honeycomb silicon nitride support.
[0063] A porous spherical alumina hydrate slurry with a solid content of 40 wt% was prepared. The slurry was prepared by mixing a porous spherical alumina precursor, deionized water, boehmite, and alumina sol at a stirring rate of 300 r / min for 60 min. The porous spherical alumina precursor had a particle size of 450 nm and an average pore size of 18 nm. The slurry was sprayed onto the pore wall surface of a honeycomb silicon nitride carrier. The coating thickness was controlled to 12 μm by adjusting the number of sprays and the solid content of the slurry. After leveling at room temperature for 20 min, the coating was pre-dried at 80 °C for 1 h to obtain the porous spherical alumina precursor composite honeycomb silicon nitride carrier.
[0064] A chloroplatinic acid and cobalt nitrate were dissolved in deionized water to prepare an impregnation solution, resulting in a Pt loading of 0.4 wt% and a Pt to Co molar ratio of 1:1. The porous spherical alumina precursor composite honeycomb silicon nitride support was placed in the impregnation solution at 50 °C for 120 min, supplemented by ultrasonic vibration at 200 W for 15 min. After impregnation, the solution was drained, centrifuged, and dried in a 60 °C oven for 16 h with a surface gas flow rate of 200 m³ / h. Subsequently, it was calcined at 650 °C for 2.5 h under a nitrogen atmosphere, followed by reduction at 380 °C for 5 h under an 8 vol% hydrogen / argon reducing atmosphere to obtain the porous spherical alumina composite honeycomb silicon nitride-based Pt-Co catalyst.
[0065] In Example 2, the honeycomb silicon nitride support provides a low pressure drop structure and thermal conductivity path, the porous spherical nano-alumina second support layer provides pore volume and loading space, and the Pt-Co type platinum-based bimetallic or multimetallic active component provides active sites for hydrogen catalytic combustion. Example 2 was used to verify the compatibility of the honeycomb high thermal conductivity substrate support, the porous spherical alumina precursor second support layer, and the Pt-Co type platinum-based bimetallic or multimetallic active component.
[0066] Example 3: This example discloses a nanorod-shaped alumina composite stainless steel Pall ring-based Pt-Cu catalyst. The specific preparation process is as follows:
[0067] 30g of Φ5mm×5mm stainless steel Pall ring support was degreased and cleaned, then washed with deionized water and dried. The stainless steel Pall ring support was then subjected to chemical etching pretreatment in a mixed acid system of hydrochloric acid and nitric acid at a volume ratio of 1:2. Both hydrochloric acid and nitric acid were prepared using commonly used analytical grade acids in the laboratory. The etching temperature was 55℃, and the etching time was 90 minutes. After etching, the support was washed with deionized water until neutral and dried at 100℃ to obtain a stainless steel Pall ring support with a micro-roughened surface structure.
[0068] A second carrier layer of nanorod-shaped alumina precursor was grown on the surface of a stainless steel Pall ring support using a sol-gel method. Aluminum isopropoxide was dissolved in isopropanol, and hydrolysis was performed with deionized water and a small amount of nitric acid to form an aluminum alkoxide sol. The viscosity of the aluminum alkoxide sol was controlled at 25 mPa·s at 25 °C. The stainless steel Pall ring support was immersed in the aluminum alkoxide sol for 1 min, then pulled at a speed of 50 mm / min, and allowed to stand at room temperature for 10 min. This immersion-pulling cycle was repeated three times to allow the aluminum alkoxide sol to adhere to the surface of the Pall ring support. Subsequently, aging, drying, and calcination were performed to form the second carrier layer of nanorod-shaped alumina. The obtained second carrier layer of nanorod-shaped alumina had a diameter of 40 nm and an aspect ratio of 6:1.
[0069] Using platinum acetylacetonate and copper acetylacetonate as precursors, Pt-Cu type platinum-based bimetallic or multimetallic active components were loaded via low-temperature vapor deposition. The deposition vacuum was 15 Pa, the deposition temperature was 240 °C, the argon carrier gas flow rate was 60 sccm, and the deposition time was 60 min. After vapor deposition, the samples were freeze-dried under vacuum at -30 °C for 20 h. Subsequently, they were calcined at 500 °C for 4 h under an argon atmosphere, and then reduced at 320 °C for 7 h under a 20 vol% hydrogen / nitrogen reducing atmosphere to obtain nanorod-shaped alumina composite stainless steel Pt-Cu cyclohexane catalyst.
[0070] In Example 3, the stainless steel Pall ring carrier provides structural support and metal thermal conduction channels, the nanorod-shaped nano-alumina second carrier layer provides open mass transfer channels, and low-temperature vapor deposition improves the uniformity of platinum-based bimetallic or multimetallic active component loading on complex structural surfaces.
[0071] Example 4: This example discloses a composite morphology alumina foam nickel-based Pt-Ru catalyst, and the specific preparation process is as follows:
[0072] 50g of 30ppi nickel foam substrate was pretreated with ultraviolet laser. The ultraviolet laser wavelength was 355nm, the pulse energy density was 2.0J / cm², the scanning speed was 200mm / s, the spot spacing was 20μm, and the number of scanning layers was 6. After laser treatment, micro-pits and etched textures were formed on the surface of the nickel foam substrate.
[0073] The laser-treated nickel foam support was placed in a hydrothermal reactor to prepare a hydrothermal system containing aluminum nitrate, urea, and morphology modifiers. The morphology modifiers were polyvinylpyrrolidone (PVP) and citric acid, with PPVD added at 2% of the mass of aluminum nitrate and citric acid added at 1% of the mass of aluminum nitrate. The hydrothermal system was held at 160°C for 8 hours to form a second support layer of spherical and rod-shaped composite alumina precursors on the surface of the nickel foam skeleton. After the hydrothermal reaction, the substrate was washed and pre-dried at 80°C for 1 hour.
[0074] A mixture of ethylene glycol containing chloroplatinic acid and ruthenium chloride was prepared to achieve a Pt loading of 0.8 wt% and a Pt to Ru molar ratio of 3:1. The mixture was refluxed at 160 °C for 4 h to load the Pt-Ru type platinum-based bimetallic or multimetallic active component onto the surface of the second support layer of the composite alumina precursor. After the reaction, a gradient-stage drying process was employed: first, natural drying at room temperature for 6 h, followed by drying under vacuum at 70 °C for 10 h, with a gas flow rate controlled at 80 m³ / h. Subsequently, calcination was performed at 700 °C for 3 h under a nitrogen atmosphere, followed by reduction at 450 °C for 3 h under a pure hydrogen atmosphere to obtain a composite alumina foam nickel-based Pt-Ru catalyst.
[0075] In Example 4, nickel foam forms a continuous metallic thermally conductive network, the composite morphology nano-alumina second carrier layer provides multiple types of anchoring points and open channels, and Pt-Ru type platinum-based bimetallic or multimetallic active components are used to improve the low-temperature hydrogen catalytic combustion activity and anti-sintering ability.
[0076] Example 5: This example discloses a nanosheet-shaped alumina composite aluminum nitride sheet-shaped support-based Pt-Pd catalyst, prepared by the following method:
[0077] Aluminum nitride sheet-like supports with a thickness of 2 mm and a side length of 10 mm were washed with deionized water and ethanol and then dried. Surface activation was performed using air plasma at a discharge power of 120 W, a working vacuum of 30 Pa, a gas flow rate of 60 sccm, and a treatment time of 15 min. After treatment, the aluminum nitride sheet-like supports were placed in a hydrothermal system containing aluminum nitrate and urea and reacted at 170 °C for 8 h to allow the in-situ growth of a second support layer of nanosheet-like alumina precursor on the support surface.
[0078] Chloroplatinic acid and palladium nitrate were dissolved in ethylene glycol to achieve a Pt loading of 0.5 wt% and a Pt to Pd molar ratio of 2:1. The pH was adjusted to 10, and the mixture was refluxed at 150 °C for 3 h to load the Pt-Pd type platinum-based bimetallic or multimetallic active component onto the surface of the second support layer of the nanosheet alumina precursor. The catalyst was then dried at 50 °C for 5 h, followed by drying at 90 °C for 10 h. After drying, it was calcined at 520 °C for 3 h in air, and then reduced at 400 °C for 4 h in a 10 vol% hydrogen / nitrogen reducing atmosphere to obtain a nanosheet alumina composite aluminum nitride sheet-supported Pt-Pd catalyst.
[0079] In Example 5, the aluminum nitride sheet support can form a shorter heat conduction path with the heat exchange structure. The nanosheet-like alumina second support layer and the Pt-Pd type platinum-based bimetallic or multimetallic active components together improve the low-temperature hydrogen catalytic combustion activity of the sheet-like catalytic combustion module.
[0080] Comparative Example 1: This comparative example uses a Pt-Ni / SiC catalyst without surface activation and without an alumina precursor second support layer. 20g of a 2mm silicon carbide support was taken, without surface activation treatment or the construction of an alumina precursor second support layer. The same chloroplatinic acid and nickel nitrate impregnation solution as in Example 1 was prepared, and the silicon carbide support was directly impregnated at room temperature for 3 hours. After impregnation, the support was centrifuged, dried at 80°C for 12 hours, then calcined in air at 550°C for 3 hours, and reduced at 420°C for 4 hours under a 10 vol% hydrogen / nitrogen reducing atmosphere to obtain a directly impregnated Pt-Ni / SiC catalyst.
[0081] The difference between Comparative Example 1 and Example 1 is as follows:
[0082] Comparative Example 1 did not undergo surface activation treatment and did not form an alumina precursor second carrier layer. Comparative Example 1 was used to illustrate the effects of a rough activated surface and a nano-alumina second carrier layer on the anchoring of platinum-based bimetallic or multimetallic active components.
[0083] Comparative Example 2: This comparative example discloses a conventional Pt / γ-Al₂O₃ catalyst. 20g of 2mm conventional γ-Al₂O₃ microspheres were used, and pretreated with nitrogen at 200℃. No high thermal conductivity substrate was used, no nano-alumina second support layer was constructed, and no alloy metal was introduced. Single-metal Pt was supported using ethylene glycol reduction, with a Pt loading of 0.6wt%. After loading, the catalyst was dried in an oven at a constant temperature, then calcined in air at 550℃, and reduced under a 10vol% hydrogen / nitrogen reducing atmosphere to obtain the single-metal Pt / conventional alumina catalyst.
[0084] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not use a high thermal conductivity substrate, does not construct a nano-alumina second carrier layer, and does not form platinum-based bimetallic or multimetallic active components. Comparative Example 2 is used to illustrate the problems of insufficient thermal conductivity of ordinary alumina carriers and insufficient anti-sintering ability of single metal Pt.
[0085] Comparative Example 3: This comparative example discloses a sheet-like alumina composite silicon carbide-based Pt catalyst. The sheet-like alumina composite silicon carbide support was prepared according to the method of Example 1, but only chloroplatinic acid was added during the platinum-based bimetallic or multimetallic active component loading stage, without adding nickel nitrate, so that the theoretical Pt loading was 0.6 wt%. The remaining conditions of ethylene glycol liquid phase reduction, gradient drying, calcination treatment and reduction activation treatment were the same as in Example 1, and the sheet-like alumina composite silicon carbide-based Pt catalyst was obtained.
[0086] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 does not introduce the alloy metal Ni. Comparative Example 3 is used to illustrate the effect of alloy metals on the stability of platinum-based bimetallic or multimetallic active components and the low-temperature hydrogen catalytic combustion performance.
[0087] Comparative Example 4: This comparative example discloses a single-temperature drying Pt-Ni catalyst. The surface activation treatment of the silicon carbide support, the construction of the second support layer of the sheet-like alumina precursor, and the loading of Pt-Ni type platinum-based bimetallic or multimetallic active components were completed according to the method of Example 1. However, the gradient drying treatment was changed to a single-temperature drying at 80°C for 14 hours. The remaining calcination treatment and reduction activation treatment conditions were the same as in Example 1, and a single-temperature drying Pt-Ni catalyst was obtained.
[0088] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 uses a single constant-temperature drying process, omitting the low-temperature shape-preserving drying stage and the medium-temperature solvent removal drying stage. Comparative Example 4 is used to illustrate the effect of gradient drying treatment on reducing precursor migration, agglomeration of platinum-based bimetallic or multimetallic active components, and enrichment on the outer surface.
[0089] Performance tests are as follows:
[0090] The catalysts obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were respectively loaded into a fixed-bed catalytic combustion reactor for performance testing.
[0091] The test conditions were: reaction space velocity 10,000 h⁻¹ -1 The hydrogen volume concentration is 3%, the equilibrium gas is air, and the heating rate is 5℃ / min. The low-temperature ignition temperature is defined as the reactor inlet temperature at which the hydrogen conversion rate first reaches 10%. The hydrogen conversion rate is calculated from the reactor inlet hydrogen concentration and the outlet hydrogen concentration.
[0092] The equivalent heat transfer coefficient characterizes the ability of a catalyst bed to transfer the heat of reaction to the heat transfer medium. The equivalent heat transfer coefficient is calculated using the following formula:
[0093]
[0094] in, The equivalent heat transfer coefficient is expressed in W·m. -2 ·K -1 ; The heat removed from the catalyst bed per unit time is expressed in W. This represents the effective heat transfer area between the catalyst bed and the heat transfer medium, expressed in m². It represents the difference between the average temperature of the catalyst bed and the average temperature of the heat exchange medium, expressed in K.
[0095]
[0096] in, The heat removed from the catalyst bed per unit time is expressed in W. The heat exchange medium mass flow rate is expressed in kg / s. The specific heat capacity at constant pressure of the heat exchange medium is expressed in J·kg. -1 ·K -1 ; This refers to the outlet temperature of the heat exchange medium, in Kelvin (K). Inlet temperature of the heat exchange medium, in Kelvin. Effective heat exchange area. The contact or heat exchange coupling area between the catalyst bed and the heat exchange wall in the fixed-bed reactor was determined; the test results are shown in Table 2.
[0097] Table 2. Catalyst performance test results:
[0098]
[0099] Table 2 shows that Examples 1 to 3 all exhibited lower low-temperature ignition temperatures, higher hydrogen conversion rates, and higher equivalent heat transfer coefficients under the same test conditions. Example 1 differs from Comparative Example 1 in that it incorporates plasma activation treatment on the silicon carbide support surface and a sheet-like nano-alumina second support layer, enabling the Pt-Ni type platinum-based bimetallic or multimetallic active component to anchor onto the surface of the nano-alumina second support layer. Example 1 differs from Comparative Example 2 in that it uses a highly thermally conductive silicon carbide substrate support, a sheet-like nano-alumina second support layer, and a Pt-Ni type platinum-based bimetallic or multimetallic active component, which simultaneously improves thermal conductivity and the stability of the platinum-based bimetallic or multimetallic active component.
[0100] Example 1 differs from Comparative Example 3 in that Ni is introduced as an alloying metal to form a Pt-Ni type platinum-based bimetallic or multimetallic active component. Test results show that the alloying metal is beneficial for lowering the low-temperature ignition temperature and improving hydrogen conversion rate. Example 1 differs from Comparative Example 4 in that a gradient drying treatment is used. Test results show that the gradient drying treatment is beneficial for reducing the migration and enrichment of metal precursors on the outer surface, maintaining a more uniform distribution of the platinum-based bimetallic or multimetallic active component.
[0101] The above test results indicate that the continuous preparation path formed by high thermal conductivity substrate surface activation, alumina precursor second carrier layer morphology construction, platinum-based bimetallic or multimetallic active component loading, gradient drying treatment, calcination treatment and reduction activation treatment can improve the low-temperature activity, thermal conductivity and heat dissipation capacity and structural stability of hydrogen catalytic combustion catalyst.
[0102] Example 6: This example discloses a cerium-zirconium co-doped nanorod-shaped alumina composite silicon carbide honeycomb-based Pt-Ni-Co multimetallic catalyst. The specific preparation method and physical mechanism verification are as follows:
[0103] A silicon carbide honeycomb substrate with a pore density of 400 cells / in² was used as a high thermal conductivity substrate. High-pressure deionized water spraying was employed to remove free dust adhering to the inner surface of the pores. The cleaned silicon carbide honeycomb substrate was then placed on a CNC vacuum stage for laser-modified surface activation. A 266nm ultraviolet picosecond laser was used as the laser source, with a single-pulse energy density set to 1.8 J / cm², a scanning speed of 150 mm / s, and a spot spacing finely adjusted to 25 μm. Eight consecutive layers of cross-scanning were performed on the inner wall of the substrate pores. The transient injection of high-frequency, short-pulse energy caused non-thermal ablation of the silicon carbide lattice surface, directly breaking the originally dense and inert lattice arrangement.
[0104] The treated high thermal conductivity substrate surface developed dense micron-scale etched defect sites and nano-scale broken dangling bonds. These broken bonds rapidly captured water molecules in the ambient air and dissociated, transforming into high-density surface hydroxyl sites, thus forming a rough, activated surface that combines geometric micro-roughness with chemical polarity.
[0105] A water bath temperature-controlled reactor equipped with a high-shear emulsifier was used. 600 mL of anhydrous isopropanol was added as a solvent, and aluminum isopropoxide was added and completely dissolved at 65°C. Under vigorous stirring, a mixed hydrolysate of deionized water and nitric acid was slowly added dropwise to induce a controlled hydrolysis-condensation reaction of the aluminum alkoxide, forming a basic aluminum sol. Cerium nitrate hexahydrate and zirconium oxychloride octahydrate were accurately weighed and dissolved in deionized water at a 1:1 molar ratio of cerium to zirconium. The resulting rare earth metal salt solution was injected uniformly into the basic aluminum sol at a rate of 1 mL / min using a high-pressure horizontal flow pump, ensuring the total molar ratio of cerium, zirconium, and aluminum in the system was locked at 0.15:1, thus obtaining a second carrier construction system containing rare earth precursors.
[0106] After continuous aging under an ultrasonic field for 8 hours, the kinetic viscosity stabilized at 35 mPa·s. The surface-activated high thermal conductivity substrate was then immersed in the second carrier construction system using a vacuum suction-lift process. A vacuum of 15 Pa was maintained for 15 minutes, allowing the sol to overcome capillary resistance and completely penetrate into the micro-pits at the bottom layer of the rough activated surface. The pressure was then restored to normal, and the substrate was vertically lifted from the liquid surface at a constant rate of 20 mm / min.
[0107] The vacuum suction and lifting operation was repeated four times. After each lifting, the sample was placed in a 110℃ constant-temperature hydrothermal reactor for in-situ saturated vapor pressure aging for 12 hours. During crystallization, aluminum source molecules grew anisotropically along specific crystal planes in the hydrothermal environment, gradually transforming into a second carrier layer of alumina precursor with a nanorod morphology. Cerium and zirconium precursors were uniformly encapsulated in the grain boundaries and interstices of the nanorod framework. The resulting nanorod structures had an average diameter of 35 nm, a length of 250 nm, and an aspect ratio of approximately 7:1, forming a complex and open three-dimensional mass transfer channel network, thus obtaining a composite carrier.
[0108] Measure 150 mL of ethylene glycol into a three-necked flask. Add chloroplatinic acid, nickel nitrate, and cobalt nitrate sequentially to prepare a loading system containing a platinum precursor and an alloy metal precursor. Set the theoretical mass loading of Pt to 0.5 wt%, and the molar ratio of Pt, Ni, and Co to 1:1:1. Use a 0.5 mol / L sodium hydroxide-urea buffer solution to strictly anchor the initial pH of the loading system to 10.5.
[0109] The composite support was immersed in the supported system. Oil bath heating was initiated, and the system temperature was raised to 165℃ using a gradient heating program, followed by continuous reflux stirring for 200 min at a stable stirring rate of 250 r / min. In the high-temperature, strongly alkaline environment, ethylene glycol molecules undergo dehydrogenation to generate diacetyl, releasing free electrons. Pt ions in the solution preferentially capture electrons and are reduced to zero-valent metal nuclei. The Pt nuclei, in a high surface energy state, induce underpotential deposition and catalytic co-reduction of surrounding Ni and Co ions. The three metal atoms undergo lattice rearrangement on the surface of the second support layer of the alumina precursor, forming a platinum-based bimetallic or multimetallic active component in the form of a Pt-Ni-Co ternary alloy phase. After the reaction, the supported catalyst was rapidly removed and washed repeatedly by centrifugation with anhydrous ethanol.
[0110] The washed, supported catalyst was transferred to a parallel-flow microwave hot air drying oven for gradient drying. The surface gas flow rate in the drying space was set to 180 m³ / h to maintain a dynamic balance of heat and mass exchange. The low-temperature conformal drying stage was maintained at 45°C for 6 hours. The extremely low evaporation rate suppressed pore collapse caused by capillary tension and prevented the ternary multi-metal particles from being carried by the solvent to the surface of the composite support for aggregation.
[0111] The heating rate for the medium-temperature solvent removal and drying stage was set at 1.5℃ / min, with a target temperature of 95℃, and drying was continued for 12 hours. Combined with high-flow-rate circulating air purging, the deep-seated ethylene glycol molecules and water molecules adsorbed inside the nanoscale pores were gradually removed, completely solidifying the three-dimensional structure of the supported catalyst and the distribution of active materials.
[0112] The gradient-dried supported catalyst was transferred into a temperature-controlled tube furnace for core thermophysical evolution. Calcination was carried out in a continuously flowing clean air atmosphere. The heating curve was strictly controlled: initially, the temperature was increased to 250°C at a rate of 2°C / min and held for 2 hours to completely pyrolyze residual nitrate and organic ligands; subsequently, the temperature was increased to 620°C at a slow ramp rate of 3°C / min and calcined at this temperature for 5 hours. This slow heating process gradually transformed the amorphous alumina precursor second support layer into a crystalline nano-alumina second support layer.
[0113] The uniformly dispersed cerium-zirconium components overcame the kinetic barrier under thermal driving force, interpenetrating through solid-phase diffusion reactions to precipitate a cerium-zirconium solid solution phase with a fluorite structure in situ. Reduction activation treatment followed, switching to a 15 vol% hydrogen / argon reducing mixed atmosphere and isothermally reducing at 350℃ for 6 h, ultimately obtaining a cerium-zirconium co-doped porous spherical alumina composite silicon carbide honeycomb Pt-Ni-Co multimetallic hydrogen catalytic combustion catalyst with high thermal conductivity.
[0114] The microscopic mechanisms of heat conduction and stress release during catalytic combustion are based on crystal lattice engineering. The microstructure of the obtained samples was determined using high-resolution X-ray diffraction, and the average lattice constant of the generated nano-alumina second carrier layer was resolved. The average lattice constant of the in-situ precipitated cerium-zirconium solid solution phase is 0.312 nm, while the average lattice constant of the in-situ precipitated cerium-zirconium solid solution phase is higher due to the lattice contraction effect caused by the partial substitution of Ce ions by Zr ions. It stabilizes at 0.325 nm. According to the lattice mismatch strain formula:
[0115]
[0116] The lattice mismatch strain of this structure was calculated. It is 4.16%.
[0117] Upon contact with a vacancy, the delocalized electron cloud on the surface of Pt-Ni-Co ternary multimetallic particles dispersed within the pores is strongly pulled and partially transferred into the vacancy orbital. This strong interaction bond, resulting from the electron donor-acceptor confinement structure, effectively locks the platinum-based bimetallic or multimetallic active components within the defect grooves of the nano-alumina second carrier layer. Even under conditions of extreme localized exothermic hydrogen catalytic combustion, the migration activation energy of metal agglomeration increases significantly.
[0118] The lattice distortion regions constitute a periodic phononic crystal defect phase. When the massive heat of reaction released by the flameless oxidation of hydrogen is transferred through the nano-alumina second carrier layer to the high thermal conductivity substrate in the form of lattice vibrations, the 4.16% lattice mismatch causes strong scattering of optical phonons. The phonon scattering effect causes the difference in thermal expansion rate between the interfaces to be absorbed by microscopic lattice dissipation, synergistically weakening the macroscopic thermal stress concentrated at the interface.
[0119] To verify the actual effect, the sample prepared in Example 6 was placed in a fixed-bed catalytic combustion reactor under the same test conditions for performance evaluation.
[0120] Table 3 shows the catalyst performance test data for Example 6:
[0121]
[0122] Test results confirm that embedding cerium-zirconium solid solution strain control into the continuous preparation path of the original invention increases the equivalent heat transfer coefficient of Example 6 to 61 W·m. -2 ·K -1 Furthermore, after the heat of reaction is generated from the Pt-Ni-Co core, it rapidly penetrates the oxygen vacancy confinement interface and the phonon scattering layer, and is three-dimensionally exported along the silicon carbide channel walls. The heat transfer chain and the catalytic reaction chain achieve deep impedance matching, which not only further lowers the low-temperature ignition temperature to 9.6℃, but also maintains the stability of the microstructure under repeated start-stop thermal shocks.
[0123] The high thermal conductivity hydrogen catalytic combustion catalyst preparation method of this invention utilizes a high thermal conductivity substrate, aluminum source, platinum precursor, alloy metal precursor, drying equipment, calcination equipment, and reduction equipment, all of which can be obtained or implemented using existing industrial equipment. The method is adaptable to spherical, columnar, sheet-like, honeycomb, foam, Raschig ring, Pall ring, and granular / block supports, and allows for parameter adjustment based on the bed pressure drop, heat transfer mode, and packing method of the hydrogen catalytic combustion reactor. The high thermal conductivity hydrogen catalytic combustion catalyst obtained by this invention can be used in fuel cell exhaust hydrogen removal devices, hydrogen energy heating devices, industrial hydrogen-containing exhaust gas treatment devices, and distributed hydrogen energy heat generation devices.
[0124] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.
[0125] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. It should be noted that any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for synthesizing a highly dispersed catalytic combustion catalyst, characterized in that, Includes the following steps: S1. Select a high thermal conductivity substrate and perform surface activation treatment on the high thermal conductivity substrate to form a rough activated surface on the surface of the high thermal conductivity substrate for the nucleation and attachment of alumina precursor. The rough activated surface has a porous structure, a rough structure and surface active sites. S2. The high thermal conductivity substrate carrier after surface activation treatment is placed in the second carrier construction system. The second carrier construction system is a reaction system for forming the second carrier layer of alumina precursor. The second carrier layer of alumina precursor is formed on the surface of the high thermal conductivity substrate carrier to obtain a composite carrier. The second carrier layer of alumina precursor has at least one morphology among nanosheet, nanorod, and porous sphere. S3. After pre-drying the composite support at 60°C to 100°C for 0.5h to 2h, the composite support is brought into contact with a loading system containing platinum precursor and alloy metal precursor, so that platinum and alloy metal form platinum-based bimetallic or multimetallic active components on the surface of the second support layer of the alumina precursor, thereby obtaining a supported catalyst. S4. The supported catalyst is subjected to gradient drying treatment to gradually remove the solvent in the supported system from the outer surface of the composite support and the surface and internal structure of the second support layer of the alumina precursor. S5. The supported catalyst after gradient drying is subjected to calcination and reduction activation treatment in sequence to transform the alumina precursor second support layer into a nano-alumina second support layer, and to form an interface bond between the platinum-based bimetallic or multimetallic active component, the nano-alumina second support layer and the high thermal conductivity substrate support to obtain a high thermal conductivity hydrogen catalytic combustion catalyst.
2. The method for synthesizing a highly dispersed catalytic combustion catalyst according to claim 1, characterized in that, The high thermal conductivity substrate is at least one of a metal-based substrate, a ceramic-based substrate, and a carbon-based substrate; the metal-based substrate is selected from at least one of copper, stainless steel, pure aluminum, aluminum alloy, nickel-based alloy, and nickel foam; the ceramic-based substrate is selected from at least one of silicon carbide, silicon nitride, aluminum nitride, hexagonal boron nitride, and high-purity alumina; and the carbon-based substrate is selected from at least one of graphite, expanded graphite, graphene, and carbon nanotubes.
3. The method for synthesizing a highly dispersed catalytic combustion catalyst according to claim 1, characterized in that, The high thermal conductivity substrate carrier has the following external structure: spherical carrier, columnar carrier, sheet carrier, honeycomb carrier, foam carrier, Raschig ring carrier, Pall ring carrier, or granular block carrier; the spherical carrier has a single sphere diameter of 0.5 mm to 10.0 mm, the columnar carrier has a diameter of 1 mm to 8 mm and a height of 1 mm to 12 mm, the sheet carrier has a thickness of 0.5 mm to 5 mm and a side length of 0.5 mm to 20 mm, the honeycomb carrier has a pore density of 200 cells / in² to 600 cells / in², the foam carrier has a pore density of 10 ppi to 60 ppi, and the granular block carrier has an equivalent particle size of 0.5 mm to 15 mm.
4. The method for synthesizing a highly dispersed catalytic combustion catalyst according to claim 1, characterized in that, The surface activation treatment described in S1 includes at least one of plasma modification, laser modification, ozone coupled roasting modification, and chemical corrosion modification.
5. The method for synthesizing a highly dispersed catalytic combustion catalyst according to claim 4, characterized in that, The plasma modification atmosphere is oxygen, argon, nitrogen or air, the discharge power is 80W to 300W, the working vacuum is 5Pa to 50Pa, the gas flow rate is 20sccm to 100sccm, the processing time is 5min to 40min, and the discharge frequency is 10kHz to 40kHz.
6. The method for synthesizing a highly dispersed catalytic combustion catalyst according to claim 4, characterized in that, The laser modification uses ultraviolet laser, picosecond laser or femtosecond laser, with a single laser pulse energy density of 0.8 J / cm² to 3.2 J / cm², a scanning speed of 100 mm / s to 350 mm / s, a spot spacing of 15 μm to 30 μm, and 3 to 12 scanning layers.
7. The method for synthesizing a highly dispersed catalytic combustion catalyst according to claim 4, characterized in that, The ozone-coupled calcination modification includes ozone pretreatment and calcination treatment; the ozone concentration of the ozone pretreatment is 80 mg / L to 150 mg / L, the treatment temperature is 25℃ to 60℃, and the treatment time is 15 min to 60 min; the atmosphere of the calcination treatment is air, nitrogen, or argon, the calcination temperature is 300℃ to 850℃, and the calcination time is 1 h to 4 h.
8. The method for synthesizing a highly dispersed catalytic combustion catalyst according to claim 4, characterized in that, The chemical corrosion modification uses hydrochloric acid, nitric acid, sulfuric acid or mixed acid corrosion system, with a corrosion temperature of 30℃ to 80℃ and a corrosion time of 20min to 120min.
9. The method for synthesizing a highly dispersed catalytic combustion catalyst according to claim 1, characterized in that, The surface of the high thermal conductivity substrate carrier after surface activation treatment in S1 meets at least one of the following conditions: the water contact angle measured by the deionized water droplet method at 25℃±2℃ is 20° to 75°; and the surface roughness Ra measured by the contact profilometer is 0.2μm to 3.0μm.
10. The method for synthesizing a highly dispersed catalytic combustion catalyst according to claim 1, characterized in that, After S2 treatment, the mass increment of the second carrier layer of the alumina precursor relative to the high thermal conductivity substrate carrier is 0.5wt% to 20wt%; the thickness of the nanosheet-like second carrier layer of the alumina precursor is 5nm to 30nm and the diameter is 100nm to 400nm; the diameter of the nanorod-like second carrier layer of the alumina precursor is 20nm to 80nm, the length is 150nm to 600nm, and the aspect ratio is 3:1 to 10:1; the particle size of the porous spherical second carrier layer of the alumina precursor is 200nm to 800nm, the average pore size is 5nm to 30nm, and the porosity is 30% to 65%.